Plasmidome-analysis of ESBL-producing escherichia coli using conventional typing and high-throughput sequencing. - Alma Brolund (Public Library of Science (PLoS), 2013)
Infections caused by Extended spectrum β-lactamase (ESBL)-producing E. coli are an emerging global problem, threatening the effectiveness of the extensively used β-lactam antibiotics. ESBL dissemination is facilitated by plasmids, transposons, and other mobile elements. We have characterized the plasmid content of ESBL-producing E. coli from human urinary tract infections. Ten diverse isolates were selected; they had unrelated pulsed-field gel electrophoresis (PFGE) types (<90% similarity), were from geographically dispersed locations and had diverging antibiotic resistance profiles. Three isolates belonged to the globally disseminated sequence type ST131. ESBL-genes of the CTX-M-1 and CTX-M-9 phylogroups were identified in all ten isolates. The plasmid content (plasmidome) of each strain was analyzed using a combination of molecular methods and high-throughput sequencing. Hidden Markov Model-based analysis of unassembled sequencing reads was used to analyze the genetic diversity of the plasmid samples and to detect resistance genes. Each isolate contained between two and eight distinct plasmids, and at least 22 large plasmids were identified overall. The plasmids were variants of pUTI89, pKF3-70, pEK499, pKF3-140, pKF3-70, p1ESCUM, pEK204, pHK17a, p083CORR, R64, pLF82, pSFO157, and R721. In addition, small cryptic high copy-number plasmids were frequent, containing one to seven open reading frames per plasmid. Three clustered groups of such small cryptic plasmids could be distinguished based on sequence similarity. Extrachromosomal prophages were found in three isolates. Two of them resembled the E. coli P1 phage and one was previously unknown. The present study confirms plasmid multiplicity in multi-resistant E. coli. We conclude that high-throughput sequencing successfully provides information on the extrachromosomal gene content and can be used to generate a genetic fingerprint of possible use in epidemiology. This could be a valuable tool for tracing plasmids in outbreaks.